Academic stress from the viewpoint of Iranian adolescents: A qualitative study - Zahra Hosseinkhani; Saharnaz Nedjat; Hamid Reza Hassanabadi; Mahboubeh Parsaeian (Wolters Kluwer Medknow Publications, 2019)
BACKGROUND: Academic stress is one of the major affecting factors on adolescent health. This study investigates adolescents' view about the sources of academic stress, with which their identification could be used for the reduction of adolescent academic stress. MATERIALS AND METHODS: This qualitative study was conducted with Directional Content Analysis methodology. Semi-structured interview methods were used for data collection. Participants were students aged 12-18 years old. Purposeful sampling with Opportunistic Maximum Variation Method was performed in terms of type of schools, socioeconomic classes, and gender of students. A total of 43 interviews and were conducted by two interviewers. RESULTS: A total of 173 codes, 11 subcategories, and 5 categories were extracted as academic stressors. The categories included family factors (32 codes); peers (18 codes); teachers, school supervisors, and educational system (72 codes); homework and test scores (32 codes); and educational assistance classes (19 codes). CONCLUSION: This study showed that students have different sources of academic stress. Awareness of their source of stress can help parents and teachers to revise their treat about students' function and policymaker to provide better planning and management for students.